ANALISIS TINGKAT LITERASI KEUANGAN - HURIYATUL AKMAL; YOGI EKA SAPUTRA (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The research theme is financial management. This study aims to measure the level of financial literacy. This study used quantitative analysis. The sample was 100 people. Financial literacy is one of the key factors in building a sound financial industry and trusted for a country. It can be seen from the commitment of developed countries to seriously manage the issue of financial literacy as a strategic part in building a strong economy. The results showed that financial literacy among respondents are in the medium category.